Analisis Kesantunan Berbahasa Dalam Film Pendek Negosiasi Kelas X Pada Saluran Youtube Cinta Bahasa - Endah Yustiani; Ninda Alifa; Widini Arti; Fairuzah Qolbi; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Kris Brantas Abiprayu (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The analysis of linguistic politeness in a short film about negotiations for class X on the Cinta Bahasa YouTube channel focuses on the analysis of politeness in negotiation activities. The purpose of analyzing linguistic politeness in the short film about class X negotiations is to find, describe, and evaluate the mistake in the dialogues in the videos titled